Resilience-based interventions in the public sector workplace: a systematic review - Malin H. L. Hollaar; Bram Kemmere; Paul L. Kocken; Semiha Denktaş (BMC Public Health)
Abstract Background Previous studies have advocated the benefits of resilience-based interventions for creating a healthy and sustainable workforce. However, resilience is defined and measured in diverse ways. Therefore, the aim of this systematic review is (1) to identify how resilience is defined within different workplace interventions, translated into intervention content, and measured in these interventions; and (2) to synthesize the effectiveness of these interventions. Methods A systematic literature search was conducted and included articles from 2013 – 2023. Twenty-four studies met the inclusion criteria, covering a total of 26 unique interventions. Definitions were categorized as: resilience as a trait, process, or outcome. Cohen’s D was calculated to depict the effect sizes within the intervention groups from pre-test to post-test and, when possible, from pre-test to 3-month follow-up. Results Included studies applied a wide range of definitions; most definitions fitted within the trait-orientation, conceptualizing resilience as an individual characteristic or ability, or the process-orientation, conceptualizing resilience as a dynamic process. No studies solely used the outcome-orientation, but some did combine elements of all three orientations. Various definitions, measures and intervention strategies were applied, however, almost half of the studies (46%) showed inconsistencies within these choices. Furthermore, findings show that most resilience-based interventions in the workplace have a positive impact. While educational workshops with a higher frequency and duration had medium to large effects, solely digital interventions had small effects, changing to small to medium when combined with non-digital elements. Conclusions Findings suggest that resilience-based can benefit employees by enhancing their psychological well-being. This, in turn, can lead to improved work-related outcomes such as productivity, thereby offering advantages to employers as well. This underscores the growing recognition that resilience should be viewed as a shared responsibility between the individual and the organization. Further advancement in the field of resilience-based interventions in the workplace calls for future research to focus on maintaining consistency when choosing a definition of resilience, developing intervention content, and choosing an outcome measure. Preregistration The search protocol was preregistered in the Open Science Framework, see Hollaar et al. (2023). https://doi.org/10.17605/OSF.IO/UKYF7 .